Būdvardžių semantikos ypatumų raiška “XX amžiaus poezijos” rinktinėje - Juzelėnienė, Saulė (Kalbotyra, 2000)
The object of the investigation is the semantics and stylistics of adjectives. Adjectives denote qualities, but qualities must be attributed to their carriers. It is common knowledge that not every quality can be attributed to any carrier, and not every carrier of a quality can be characterised by any quality. Therefore, the semantics of the adjective influences first and foremost its collocability with words designating the carrier of the quality. Inherent adjectives fall into two major groups - absolutely and relatively inherent adjectives. The semantic structure of the relatively inherent adjectives contains two principal components: the undifferentiated inherent quality and a quantifier which describes the quality in relation to the average norm which depends on the carrier of the quality, the recipient experiencer and the circumstances of perception. The functional difference between the relatively and absolutely inherent adjectives consists in the ability of the former to collocate with the infinitive and the dative denoting the perceiver. The absolutely inherent adjectives do not collocate either with the infinitive or the dative. Non-inherent adjectives denote qualities which can be attributed to non-substance. The non-inherent adjectives fall into a number of semantic groups such as epistemic, modal and evaluating adjectives, the latter subsuming two subgroups: adjectives of subjective and objective evaluation. The analysis of the semantics of the Lithuanian adjectives (based on the data from the Lithuanian collection of poetry) has revealed that the relation of quality to its carrier is the most important factor which determines the semantics of qualitative adjectives. Substance and insubstantiality are the most important semantic categories distinguished in the carriers of qualities, which have a major relevance for the study of the semantics of qualitative adjectives. The relation of a quality to the perceiver can be used as a basis for further subcategorization of inherent and non-inherent adjectives.